Acute Toxicity and Antioxidant Ability of Senegalia greggii Seed Extract - Rawand Burhan Abdul raheem (Genius Journals, 2022)
Senegalia greggii plant used as medicinal plant, it has many chemical components not known the toxicity effect. This study aimed to investigate the acute toxicity of Senegalia greggii seed Extract. Four groups of 10 rats in each group orally administration ofvarious doses of S. greggi seed extract at single dose. After 14 days of dose administration all rats were given high dose of enthused, kidney and liver for histopathological examination and collect blood for antioxidant marker. The results revealed all the rats were increased in the weight at dose depended manner, the histopathological examination for liver and kidney was shown normal hepatic structure but minimal inflammatory cell infiltration. And the administration of extract was lead to increase in the level of antioxidant enzyme GSH but, decreased in the level of MDA in the treated rats. The concluded that the S. greggi seeds ethanol extract was safe at a dose of 1000 mg /kg and has antioxidant effect to be used for medicinal purposes.
Keywords: Sanegalia greggi; Acute toxicity; GSH